Integrating Self-Assessment in Learning Vocabulary: A Quasi Experimental Research at a Vocational High School - Rosita, Mila; Thamrin, Nur Sehang; Wahyudin, Wahyudin; Abd Kamaruddin (LPPM Universitas Advent Indonesia, 2025)
This study examines the lack of English vocabulary in students, especially in nouns and verbs. This study aims to analyze the effect of self-assessment method on grade XI students of SMK Negeri 1 Mepanga. The research method used was quasi-experimental using pretest-posttest. The research sample consisted of 71 students who were divided into experimental group (34 students) and control group (37 students) as samples using total sampling technique. Data analysis using the Mann-Whitney test (SPSS 24). The Mann-Whitney test is used to compare two independent groups with ordinal or interval data that are not normally distributed. The test results show that the test statistic is 0.001, which is smaller than 0.05, meaning that the null hypothesis is rejected, and the alternative hypothesis is accepted. It can be concluded that there is a significant difference between the control class and the experimental class. This finding shows that the self-assessment method can improve students' English vocabulary. This research contributes to the development of learning strategies that can be applied to build higher order thinking skills in EFL students. The results of this study provide valuable insights for students, teachers, and future researchers.